Sugar profile and enzymatic analysis of stingless bees honey collected from local market in Malaysia - W. N., Julika; A., Ajit; N., Ismail; N., Aqilah; A., Naila; A. Z., Sulaiman (IOP Publishing, 2020)
Commercial honey is widely available in the market, raising questions whether the honeys are good in quality or otherwise, Thus, this research was designed to compare the quality of harvested stingless bee honey and commercial honey available in the Malaysian market by measuring their sugar profile and enzyme activity. The analysis showed that the honey contained moisture between 16.6% - 32.1%, various sugar starting with fructose (15.03 – 48.44 g /100 g), glucose (12.16 – 40.09 g/100 g), sucrose (<0.01 – 7.29 g/100 g), Fructose + Glucose (F+G) (15.03- 80.25 g/100 g), Fructose/Glucose (F/G) (0.78 – 1.63), and G/W (0.47 – 1.89). Also, diastase activity and Invertase activity of the honey varied from 1.82 to 6.11 DN and 0.27 IN to 4.94 IN, respectively. This research is expected to contribute and generate information to the extension of quality parameter of stingless bee honey that may help to protect consumer from purchasing adulterated honey. Though the sugar profile standards are already established in Malaysian stingless bee standard, the data obtained in this research are significant due to diversity of stingless bee species in Malaysia.